Influence of blade deflections on wind turbine noise directivity. Issue 1 (1st April 2022) - Bresciani, A P C; Boatto, U; Le Bras, S; Bonnet, P; de Santana, L D
Abstract: This paper establishes the effect of blade deflections on wind turbine noise directivity. Fast turn-around methods are used in a framework of integrated aeroelastic and aeroacoustic simulations: the blade element momentum theory is coupled with a RANS-informed Amiet's model for the aeroacoustic modelling of trailing- and leading-edge noise. This approach is applied to the NREL 5 MW wind turbine and the results of rigid and flexible blades are compared. The overall sound pressure level computed with flexible blades increases up to 13 dBA for listeners close to the rotor plane. This effect is attributed to the flapwise angular deflection of the wind turbine blade. Furthermore, the symmetry of the results with respect to the rotor plane is lost when the flapwise deflection is considered, indicating that the modelling of this rotation is of fundamental importance for the acoustic simulation.